Crosslinking induced photoluminescence quenching in polyvinyl alcohol-carbon quantum dot composite. (June 2019) - Hoang, Q.-B.; Mai, V.-T.; Nguyen, D.-K.; Truong, D.Q.; Mai, X.-D.
Abstract: Highly luminescent and water-soluble carbon quantum dots (CQDs) have been integrated into polyvinyl alcohol (PVA) recently to realize composites with synergistic functionalities. The effects of chemical interactions between CQDs and PVA matrix on the changes in optical properties of CQDs or physicochemical properties of PVA are yet to be investigated fully. Herein, we first synthesized CQDs with different surface chemistry via varying the molar ratio between citric acid (CA) and ethylenediamine and then embedded the CQDs into PVA with or without additional CA crosslinking. Infrared and UV–vis studies on CQDs and composites showed that condensation between CQDs and PVA induced a redshift in the absorption peak originating from CQDs' surface fluorophore groups. Interestingly, CA crosslinking significantly increased the water resistance, but it quenched the photoluminescence of composites. The quenching effects were reduced by using CQDs having less reactivity with CA. Highlights: Carbon quantum dots (CQDs) with different surface chemistry were synthesized. Condensation between CQDs and polyvinyl alcohol (PVA) redshifts the absorption band of surface fluorophore. Crosslinking CQD-PVA composite with citric acid quenches photoluminescence (PL). Surface tension–induced PL quenching mechanisms are proposed. The quenching effects are less pronounced with CQDs having more acidic surfaces.